2004
DOI: 10.1002/pssb.200302045
|View full text |Cite
|
Sign up to set email alerts
|

Structural, electronic and optical calculations of Cu(In,Ga)Se2 ternary chalcopyrites

Abstract: In this work, we have investigated the structural, electronic and optical properties of the ternary I -III -VI 2 chalcopyrite semiconductors ABX 2 (A = Cu, B = In, Ga, X = Se) by means of a first-principles densityfunctional total-energy calculation with the local-density approximation (LDA), using the all-electron full-potential linear-augmented plane-wave method (FP-LAPW). The equilibrium lattice constants and the bulk moduli (a, c, c/a, u and B 0 ) are compared with other theoretical calculations. The ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 32 publications
3
25
0
Order By: Relevance
“…Equation for the imaginary part of the frequency dependent dielectric function ε 2 (ω) for cubic structures is given by Belhadj et al [23]:…”
Section: Dielectric Functionmentioning
confidence: 99%
“…Equation for the imaginary part of the frequency dependent dielectric function ε 2 (ω) for cubic structures is given by Belhadj et al [23]:…”
Section: Dielectric Functionmentioning
confidence: 99%
“…Recently, the authors reported the physical properties of CuInSe 2 and its feasibility for hydrogen photocathode [7]. In extension, we present the work relative to CuIn 3 Se 5 which is usually n-type and both VB and CB are associated with Se: 4p orbital [8]. With a gap (Eg) of w1.2 eV [9], near to the optimal value required for terrestrial applications and the foregoing features, CuIn 3 Se 5 appears attractive for the solar energy conversion.…”
Section: Introductionmentioning
confidence: 99%
“…With an optical gap (Eg) averaging 1 eV [10] close to the optimal value required for terrestrial applications and the foregoing characteristics, CuInSe 2 (CISe) looks like promising one for photovoltaic cells whether liquid [11] or solid junctions [12]. CISe can be made p-type by copper deficiency and both VB and CB are associated mainly with Se: 4p orbital [13]. Photoelectrons in CB have enough negative potential to reduce water into gaseous H 2 even in strongly basic solutions.…”
Section: Introductionmentioning
confidence: 99%